Mediation of the association between obesity and osteoarthritis by blood pressure, vessel wall stiffness and subclinical atherosclerosis. (21st December 2020) - Loef, Marieke; van der Geest, Rob J; Lamb, Hildo J; de Mutsert, Renée; le Cessie, Saskia; Rosendaal, Frits R; Kloppenburg, Margreet
Abstract: Objective: We investigated the role of blood pressure, vessel wall stiffness [pulse wave velocity (PWV)] and subclinical atherosclerosis markers [carotid intima-media thickness (cIMT), popliteal vessel wall thickness (pVWT)] as mediators of the association of obesity with OA. Methods: We used cross-sectional data from a subset of the population-based NEO study ( n  = 6334). We classified clinical hand and knee OA by the ACR criteria, and structural knee OA, effusion and bone marrow lesions on MRI ( n  = 1285). cIMT was assessed with ultrasonography. pVWT was estimated on knee MRI ( n  = 1285), and PWV by abdominal velocity-encoded MRIs ( n  = 2580), in subpopulations. Associations between BMI and OA were assessed with logistic regression analyses, adjusted for age, sex and education. Blood pressure, cIMT, pVWT and PWV were added to the model to estimate mediation. Results: The population consisted of 55% women, with a mean (s .d .) age of 56(6) years. Clinical hand OA was present in 8%, clinical knee OA in 10%, and structural knee OA in 12% of participants. BMI was positively associated with all OA outcomes. cIMT partially mediated the association of BMI with clinical hand OA [10.6 (6.2; 30.5)%], structural knee OA [3.1 (1.9; 7.3)%] and effusion [10.8 (6.0; 37.6)%]. Diastolic blood pressure [2.1 (1.6; 3.0)%] minimally mediated the association between BMI and clinical knee OA. PWV and pVWT did not mediate the association between BMI and OA. Conclusions: cIMT and diastolic blood pressure minimally mediated the association of BMI with OA. This suggests that such mediation is trivial in the middle-aged population.